Osteochondral Allograft Transplants for Large Trochlear Defects - Mark E. Cinque, B.S., M.S.; Nicholas I. Kennedy, M.D.; Gilbert Moatshe, M.D.; Gustavo Vinagre, M.D.; Jorge Chahla, M.D., Ph.D.; Zaamin B. Hussain, B.A.; Robert F. LaPrade, M.D., Ph.D. (Arthroscopy Techniques, 2017)
Focal articular cartilage injuries in the knee are common and can cause severe morbidity and reduced function. The articular cartilage is avascular and has limited ability to heal, and hence, patients with cartilage injuries have increased risk of progressing to osteoarthritis. Most of the cartilage injuries are located on the femoral condyles. Engaging focal cartilage injuries involving the trochlea are challenging because of the morbidity caused by these injuries and the limited treatment options. Osteochondral allograft transplantation is emerging as a promising treatment for full-thickness articular cartilage defects. Recent studies have reported high success rates with the use of osteochondral allografts. This article reports our technique of osteochondral allograft transplantation for the treatment of a focal full-thickness defect of the trochlea.